Trend Pattern of LQ45 Stocks Based on the Chi-Square Test - Efron Manik (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the relationship between the opening price and the closing price of stocks listed in the LQ45 index on the Indonesia Stock Exchange during the period of March to May 2026. Daily stock data were classified into three categories (negative, neutral, and positive) and subsequently analyzed using the Chi-Square test along with Cramer’s V as a measure of association. The results reveal a Chi-Square value of χ² = 293.48, which is statistically significant at the 5% level, indicating the presence of a relationship between the two variables. Furthermore, the Cramer’s V value of 0.248 suggests that the strength of this relationship falls within the weak to moderate range. Standardized residual analysis uncovers a strong persistence pattern, where the direction of stock prices at the opening tends to continue through to the closing, alongside a relatively low occurrence of price reversals. These findings imply that the opening price can serve as an early indicator of the likely direction of the closing price, although it remains influenced by other market factors.